Penerapan Metode Branch and Bound untuk Optimalisasi Rute Wisata Terdekat di Kota Palembang - Jaysen Stephanus; Felix Gunawan; Yohannes Yohannes (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
This study discusses the application of the Branch and Bound method to optimize the nearest tourist route in Palembang City using the Traveling Salesman Problem (TSP) approach. The problem raised is how to determine the most efficient tourist route from several tourist destinations with minimum travel distance. The study utilizes geographic coordinate data of tourist destinations obtained through OpenStreetMap, then the distance between locations is calculated using the Haversine Formula to obtain an accurate distance estimate based on latitude and longitude. Furthermore, the Branch and Bound Algorithm is used to find the optimal route solution through the process of branching, bounding, and pruning so that the solution search becomes more efficient than the brute force method. The results show that the system successfully produces an optimal circular tourist route with a total minimum distance of 40.47 km and an execution time of 12.84 seconds. The integration of the Haversine Formula and Branch and Bound is proven to be able to provide efficient, accurate, and adaptive tourist route recommendations to help tourists save travel time and transportation costs in Palembang City.